Diffusion of Innovation Analysis of The Sayang Warga App in Surabaya’s PHBS Program - Zahrany, Asyifa; Notobroto, Hari Basuki; Raden Ajeng Chandra Kusumawardhani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: The Surabaya City Government launched the Sayang Warga (Citizens' Love) application as a means of real-time data collection and reporting of PHBS indicators to support the Clean and Healthy Living Behavior (PHBS) Program. However, its implementation faced various technical and non-technical obstacles that impacted data quality. Objective: This study aims to identify the implementation challenges of the Sayang Warga application and analyze their root causes and alternative solutions based on the Diffusion of Innovation Theory perspective. Methods: This qualitative descriptive study used a health information system evaluation approach at the Surabaya City Health Office and involved seven informants, including Puskesmas heads, officers, and health office staff. Data were collected through interviews, observations, and document reviews and were analyzed thematically. Problem prioritization used the USG method with FGDs, followed by fishbone analysis and interpretation using the Diffusion of Innovation Theory. Results: The study identified obstacles in implementing the “Sayang Warga” application within the Surabaya City PHBS program, particularly related to complexity, compatibility, observability, and the innovation diffusion stages of knowledge and confirmation. The main issue was the absence of a feature to distinguish between inputted and non-inputted data, leading to potential duplication. Conclusion: A system update is recommended to include an automatic data cleansing feature and a warning notification for duplicate inputs or unsaved data. This innovation is expected to enhance data validity, efficiency, and overall quality of PHBS reporting, thereby supporting the optimization of the Surabaya City health information system.